(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Cashew nut shell (CNS), on the other hand, has been studied extensively for pyrolysis product distribution and oil characteristics. The total oil extracted from CNS accounts to more than 95% of theoretical oil yield. The oil has unique characteristics unlike other pyrolysis oil, with a heating value of 40 MJ/kg, comparable to fuel oil and double to that of other pyrolysis oils. The unique structure found having long (C6-C15) linear chain as a head and phenolic group in the tail, in CNS oil, gives the excellent solubility in diesel, as well as in other biomass pyrolysis oils. The oil has an amazingly high stability at room temperature. A blending of high proportion of CNS oil / cardanol has been found to improve the properties like calorific value, viscosity and pH of bagasse pyrolysis oil, while the stability of the blend is being taken care by addition of as low as 5 wt. % ethanol in combination.